Cross-layer multi-channel MAC protocol combined with QoS search for cognitive wireless multi-hop networks - Jie SUN; Wei GUO (Tongxin xuebao)
In cognitive wireless multi-hop networks,the spectrum resources are highly variable and diverse.A cross-layer multi-channel MAC protocol combined with QoS search was proposed.The protocol combines the on-demand QoS search with dynamic spectrum allocation via cross-layer method,which only permits the transmission nodes to participate in the spectrum allocation and can guarantee the allocation results meet the QoS requirement.Besides,frequency division duplex transceivers are introduced to continuously listen to the common control channel,and an access algorithm is carefully designed to realize hybrid communication between nodes with erent number of transceivers.Extensive simulations show that our protocol can efficiently guarantees the QoS requirement for end-to-end transmission and significantly improves end-to-end throughput and delay.